(untitled) (Studia Prawnicze / The Legal Studies, 2012)
Wpływ czasu na formowanie i ewolucję zasad prawa międzynarodowego nie jest zjawiskiem prawu nieznanym. Wymiar czasowy leży u podstawy całej koncepcji prawa, prawa międzynarodowego w szczególności. Jednakże „klasyczne” prawo międzynarodowe znało jedynie jedną koncepcję doktrynalną uwzględniającą istnienie elementu czasowego prawa, a mianowicie prawo intertemporalne. Potrzeba uwzględnienia elementu czasowego prawa spowodowała konieczność wyjścia poza traktowane wąsko prawo intertemporalne stricto sensu. Zaczęto rozpatrywać proces stanowienia prawa i ewolucji norm prawnych z perspektywy upływu czasu lub używając określenia „progresywny rozwój” prawa międzynarodowego. Z czasem zaczęto dostrzegać, że prawo międzynarodowe musi być postrzegane jako otwarty i dynamiczny system, zdolny do wyjścia naprzeciw zmieniającym się potrzebom wspólnoty międzynarodowej. The article presents an analysis of continuing situations stricto sensu, with the main focus on the domain of human rights. The concept finds its application in circumstances where there is a continuum between the past and presence. Despite the fact that it traces back to the 19th century, the exact scope of its application as well as the legal consequences are disputable. The purpose of this analysis is to indicate the legal aspects that have to be taken into account while assessing this continuity. The author provides an overview of the relevant case-law of international courts: the Permanent Court of International Justice, European Court of Human Rights and International Court of Justice. Due to the fact that the possibility of continuing situations was foreseen by the International Law Commission, the paper refers to Article 14 of its Draft Articles on State Responsibility. The author argues that the case-law developed by international judicial organs on the basis/or in reference to international human rights treaties reflects the understanding of continuing situations in general international law. However, the key factor allowing to classify a situation as a continuing one refers to identifying the legal aspects of the continuity. Consequently, the following elements are of crucial importance in the discussion: the scope of the international obligation, the acts/or facts constituting the alleged interference in the right, date of commission of the interference, as well as the special circumstances of the case. Taking into account the evolving character of obligations incumbent upon states in the field of human rights, the concept of continuing situations may have significant effect on the accountability of certain acts for states and, as a result, increase the protection of potential victims.